FAKTOR – FAKTOR YANG BERHUBUNGAN DENGAN PELAKSANAAN INISIASI MENYUSU DINI (IMD)OLEH BIDAN - Julita Nuliana; Vitria Komala Sari (Maternal Child Health Care, 2022)
Early Breastfeeding Initiation has a positive impact on mothers and the baby itself.It has an important role in supporting the growth, health and survival of babies because it is rich in nutrients and antibodies. In 2017, in West Sumatra, there was 3.8% of Early Breastfeeding Initiation for an hour, less than 1 hour for about 45.5% and after the baby's born was around 50.7%. The purpose of this research was to find out some factors related to the implementation of early breastfeeding initiation by Midwives in BPM Community Health Center of Nilam Sari in Bukittinggi 2018. This type of research was qualitative research. The data were collected through in-depth interviews to 12 informants. They were 9 mothers and 3 midwives. The results of this research were obtained that in terms of input, the midw ife had good knowledge about Early Breastfeeding Initiation and they had a good attitude regarding Early Breastfeeding Initiation (IMD). From maternity mothers, they had lack of knowledge and attitude about Early Breastfeeding Initiation. Whereas, in terms of the process of the three dimensions studied, it had fulfilled patient expectations. There were 6 people said their babies were carried out early breastfeeding and 3 people said their babies were not carried out early breastfeedingbecause of certain things. In conclusion Early Breastfeeding Initiation had been carried out well in BPM Nilam Sari Health Center. It is suggested that the midwives improve services and quality to implement the Early Breastfeeding Initiation so that all officers can provide quality services.  Keywords : Early Breastfeeding Initiation, Midwife